Perancangan Sistem Informasi Perpustakaan Pada SMP N 1 Merlung Kabupaten Tanjung Jabung Barat - Wiwik Angrayadi; Pareza Alama Jusia; masgo (Jurnal Informatika Dan Rekayasa Komputer(JAKAKOM), 2023)
The library service process at SMP Negeri 1 Merlung still uses a manual system and has not fully utilized technology in book borrowing processes, book data management, and member data management. This often leads to errors in recording and managing book data in the library, making the library service process less effective. The purpose of this study is to design an information system that can manage library information data at SMP Negeri 1 Merlung using SLiMS. The author developed the system using the waterfall method and used the Unified Modeling Language (UML) approach with use case diagrams, activity diagrams, and class diagrams. The library information system at SMP Negeri 1 Merlung was designed using the Senayan Library Management System, also known as SLiMS 9 Bulian. The aim of this system design is to help librarians manage books and library members. The difference from the previous system implemented at SMP Negeri 1 Merlung is the more complete features, accessible by students to facilitate viewing book availability, and a more attractive interface.